PENGARUH PENGENAAN PAJAK PERTAMBAHAN NILAI DAN PAJAK KENDARAAN BERMOTOR DENGAN TARIF PROGRESIF TERHADAP DAYA BELI KENDARAAN BERMOTOR DI DENPASAR - I Dewa Made Sutedja (STIE BIITM, 2019)
Tax is an obligation that must be paid by both private and public entities of income or earnings to the government aimed at development activities in all fields. To this research to study the effect of the imposition of value added tax and motor vehicle tax at progressive rates on consumer purchasing power and the sampling technique used purposive sampling. The office SAMSAT Denpasar city as a place of study covers an area of Denpasar North, East, West and South by making consumers taxpayers as much as 100 people in the sample with slovin method. Multiple linear regression analysis technique is done with the results of the imposition of value added tax and motor vehicle tax at progressive rates on consumer purchasing power has a significant negative impact. The imposition of value added tax and motor vehicle tax with progressive of them has a negative impact on consumer purchasing power.